Fuzzy methodology application for failure analysis of transmission system. (2018) - Panchal, Dilbagh; Jamwal, Umesh; Srivastava, Priyank; Kamboj, Kushal; Sharma, Rohit
The aim of this research work is to propose a fuzzy methodology-based integrated framework for the failure analysis of the transmission system of the TATA Company-made heavy commercial vehicle. Under the failure analysis failure mode effect analysis (FMEA) approaches has been applied and the critical components of the considered system were identified on the basis of their risk priority number (RPN). The identification of critical components on the basis of RPN score results in confusion to system analyst as it becomes difficult to allocate appropriate risk priorities under same RPN scores. Also, importance among the probability of occurrence of failure (Of ), severity (S), probability of non-detection (Od ) are assumed to be of same importance, however, in real practical application there exists relative importance among these three factors. Therefore, to overcome such types of limitations of FMEA approach a fuzzy decision making system (FDMS) and grey relation analysis (GRA) approaches were applied. The ranking results so obtained were compared for better and intelligent decision making of risky components and the results were further supplied to maintenance management/reliability engineer of the considered system for planning and implementing the suitable maintenance policy accordingly.